Referee Review on a Monograph - Nickelson, L.; Ašmontas, S.; Mališauskas, V.; Šugurovas, V. (Elektronika ir Elektrotechnika, 2008)
This book contains the author theoretical and experimental investigations of open circular cylindrical gyrotropic waveguides. The book consists the detailed solutions to Maxwell’s equations for open gyrotropic or layered gyrotropic-dielectric waveguides.